Detection of poliovirus antigen by enzyme immunoassay. - Ukkonen, P (1986)
A solid-phase enzyme immunoassay (EIA) was developed for the detection of poliovirus antigen. Rabbit and guinea pig antisera for the assay were raised against purified poliovirus type 3/Fin (strain 3/Fin/K) isolated from a fecal specimen from a meningitis patient during an outbreak of poliomyelitis in Finland in 1984. The EIA was highly specific for poliovirus type 3, and it was about 30 times more sensitive for strain 3/Fin/K than for strain 3/Saukett used in the inactivated poliovirus vaccine. The sensitivity of the EIA was 2 to 5 ng of purified strain 3/Fin/K per ml, whereas disrupted viruses and soluble viral proteins were almost undetectable by the assay. Only 5 of 51 (10%) stool specimens containing poliovirus type 3/Fin detected by virus isolation were positive by the EIA. Quantitation by the EIA, using purified poliovirus 3/Fin/K as a standard, revealed that concentrations of poliovirus type 3 in undiluted fecal specimens of patients with natural poliovirus infection were only 50 ng/ml or less. In conclusion, owing to the small amount of poliovirus in feces, the EIA is not suitable for the diagnosis of poliovirus infections directly from clinical specimens, but it can be used to detect, type, and quantitate poliovirus antigen in infected cells.